Symptom Burden and Quality of Life in Long-Term Survivors with Head and Neck Cancer - Gostian, Magdalena; Allner, Moritz; Rak, Atina; Balk, Matthias; Rupp, Robin; Ostgathe, Christoph; Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Objectives: In this study, long-term survivors of head and neck cancer (HNC) were evaluated regarding their symptom burden and quality of life (QoL). Methods: This prospective study was performed during the regular follow-up consultations at one of Germany’s largest tertiary referral centers for HNC. The assessment included demographic, clinical, and oncological data, as well as the MIDOS(2) and the University of Washington Quality of Life Questionnaire (UW QoL) questionnaires. Patients were subdivided based on their disease stage, that is, early cancer stages (UICC I/II) and advanced cancer stages UICC (III/IV). Results: Between January 1, 2019 and December 31, 2019, 212 HNC patients with a mean follow-up of 46.36 ± 43.64 months were included (120 patients UICC stage I/II (22.5% female, mean age 61.93 ± 12.38 years) versus 92 patients UICC stage III/IV (25.0% female, mean age 63.73 ± 11.74 years)). For all patients evaluated (UICC I/II versus III/IV), the three most common symptoms were tiredness (47.5 vs 60.9%, P =.073, r =.123), anxiety (35.8 vs 32.6%, P =.624, phi =.034) and drowsiness (35.0 vs 44.6%, P =.157, phi =.097). Patients diagnosed with UICC III/IV stages reported loss of appetite significantly more frequently and with a high level of severity (15.0 vs 32.6%, P =.002, phi =.157; 0.23 ± 0.60 vs 0.47 ± 0.78, P =.003, r =.203). The overall symptom burden was low with a severity sum score (min 0-max 30) of 3.04 ± 3.29 versus 3.58 ± 3.38 (P =.143, r =.100). All patients rated their QoL as good (65.67 ± 20.93 vs 59.56 ± 22.00, P =.043, r =.139). Conclusion: The overall symptom burden of long-term survivors of HNC is encouragingly low. Trial registration: The study was registered in the German Registry for Clinical Studies (application No.: 00017122). Date of registration: 15.08.2019. https://drks.de/search/de/trial/DRKS00017122.
CRIS-Team Scopus Importer:2025-02-04
Keywords: head and neck cancer; MIDOS(2); patient-reported outcome; quality of life; symptom burden; UW QoL